2018
DOI: 10.1002/cjce.23152
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and toxicity of lanthanum and neodymium in horticultural plants (Brassica chinensis L. and Helianthus annuus L.)

Abstract: The dose‐response of two horticultural plant species (Brassica chinensis L., and Helianthus annuus L.) to two light Rare Earth Elements (REEs), namely lanthanum and neodymium, in‐vitro, was investigated. The phytotoxicity of the studied REEs was determined by measuring the aboveground and belowground biomass of the plant parts, and the chlorophyll production. Based on these measurements, inhibition concentration causing 50 % decrease (IC50) in plant biomass and total chlorophyll were calculated. Moreover, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 55 publications
(102 reference statements)
2
11
0
Order By: Relevance
“…The results showed that La and Ce uptake increased in H. annuus shoots and roots with the increasing concentrations of REEs in the nutritive solutions in comparison to the control ( Figure 2 ), with the roots being the preferential REE accumulation organ. The obtained results are in agreement with the trials of Rezaee et al [ 44 ], whose results showed that the accumulated La and neodymium (Nd) were higher in the roots of H. annuus and Brassica chinensis . Milania et al [ 13 ] also demonstrated that Ce accumulation is usually lower in shoots.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The results showed that La and Ce uptake increased in H. annuus shoots and roots with the increasing concentrations of REEs in the nutritive solutions in comparison to the control ( Figure 2 ), with the roots being the preferential REE accumulation organ. The obtained results are in agreement with the trials of Rezaee et al [ 44 ], whose results showed that the accumulated La and neodymium (Nd) were higher in the roots of H. annuus and Brassica chinensis . Milania et al [ 13 ] also demonstrated that Ce accumulation is usually lower in shoots.…”
Section: Resultssupporting
confidence: 92%
“…Milania et al [ 13 ] also demonstrated that Ce accumulation is usually lower in shoots. Since a metal hyperaccumulator plant should highly tolerate and accumulate more than 1000 mg·kg −1 of a metal in its aerial part and should have a translocation factor greater than 0.2 [ 44 ], H. annuus could not be considered as a potential hyperaccumulator species of La and Ce under the tested conditions. In fact, generally, to reduce metal toxicity, plants can minimize the metal translocation from the root system to the aerial parts [ 44 ], and the elevated retention of toxic metals in roots presents an acquired tolerance strategy in plants in order to protect the photosynthetic apparatus.…”
Section: Resultsmentioning
confidence: 99%
“…There are publications about phytotoxicity of some other Nd compounds. Rezaee et al (2018) reported that low concentrations of Nd (applied as Nd2O3) stimulated the development of leaves of B. chinensis L. and also increased the concentration of chlorophyll.…”
Section: Introductionmentioning
confidence: 99%
“…REE(III) as a series of non-essential heavy metal elements for living organisms affect the growth of plants (Gonzalez et al, 2014). For example, it was reported that REE(III) can improve the germination, photosynthesis, biomass, uptake of nutrition, dry weight of plants (Ramírezolvera et al, 2018; Vilela et al, 2018), and also exhibit toxic effects on plants (Joonas et al, 2016; Rezaee et al, 2018). More seriously, plants are the primary producers of the ecosystem, and can absorb and accumulate REE(III) from water, soil and atmosphere (Wang et al, 2014a; Zhuang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%